THE UNEVENNESS OF THE THREADS IN TERMS OF LINEAR DENSITY STUDY - Tojimuradov Sardor Ilxom ugli; Samiyeva Nuriniso Baxtiyorovna (Academia Science Repository, 2023)
In this article, the effect of unevenness in the thread on the product zero indicators is analyzed The quality indicators of the thread used in the production of textile products ensure the quality of the product made from it. For this reason, it is possible to obtain beautiful, elegant fabrics only when the quality indicators of the spun yarn are high.It is important to analyze the irregularities in the yarn and their causes. Unevenness in yarn can be controlled by controlling the properties of the raw materials used in the spinning plant and the technological process. The technological parameters of the raw material used in the spinning process ensure the strength of the thread obtained from it. Therefore, it is necessary to use a modern measurement system that works with high accuracy in determining fiber parameters today.